2022
DOI: 10.1073/pnas.2200348119
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors unleash pathogenic immune responses against the microbiota

Abstract: Immune checkpoint inhibitors (ICIs) are essential components of the cancer therapeutic armamentarium. While ICIs have demonstrated remarkable clinical responses, they can be accompanied by immune-related adverse events (irAEs). These inflammatory side effects are of unclear etiology and impact virtually all organ systems, with the most common being sites colonized by the microbiota such as the skin and gastrointestinal tract. Here, we establish a mouse model of commensal bacteria–driven skin irAEs and demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 91 publications
1
33
0
Order By: Relevance
“…One additional factor that might be shaping the T RM cell pool primarily is microbial antigen presentation, which is particularly important in barrier organs such as skin and intestine. In a mouse model, novel commensals in combination with ICB triggered a T cell–mediated irAE dermatitis, with the vast majority of the bacteria-specific T cells being T RM cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…One additional factor that might be shaping the T RM cell pool primarily is microbial antigen presentation, which is particularly important in barrier organs such as skin and intestine. In a mouse model, novel commensals in combination with ICB triggered a T cell–mediated irAE dermatitis, with the vast majority of the bacteria-specific T cells being T RM cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Defining these pathways provides opportunities to develop specific therapeutic interventions. A recent study using preclinical models has shown that anti–CTLA-4 therapy activates microbiome-specific T cells in the skin ( 35 ). Therefore, it is also possible that the Trm population expanding in our patients is likely specific for gut microbial antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, more work is needed to sort out their exact role in patients with low IL-2 ( Gaborit et al., 2020 ; Gao et al., 2022 ). Similarly, IL-17-producing T cells that are associated with hyperactive and pathogenic immune responses are induced in the presence of commensals such as staphylococcal species specifically upon the use of immune checkpoint inhibitors ( Hu et al., 2022 ). This raised concerns over whether all commensal-specific immune responses are pathogenic in the context of anti-tumor therapy and how cancer patients would fare on Th17 stimulating vaccines.…”
Section: Immune Dysfunctions Imposed By S Aureusmentioning
confidence: 99%